2023
DOI: 10.1080/15384047.2023.2205342
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 promotes lymphatic metastasis via activating RhoA and Rac1 pathway and predict prognosis to some extent in tongue cancer

Abstract: Background Oral tongue cancer is an extremely malignant tumor with high rate of lymphatic metastasis. Little is known about its invasion and metastasis mechanisms so far. Methods To clarify the main role of CCL2 in tongue cancer progression, we performed Transwell migration assay to confirm the effects of different concentrations of CCL2 on the migration and invasion of tongue cancer cells. Next, by siRNA interference of RhoA and Rac1 in LNMTca8113 cells, we are able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Conversely, CCL2-activated macrophages also secrete tissue repair factors, such as TGF-β and VEGF [31]. Numerous studies have shown that the overexpression of CCL2 amplifies many cancer cells' motility and promotes tumor development and metastasis [32][33][34][35][36][37][38], such as chondrosarcoma [22], nasopharyngeal carcinoma [21], and breast carcinoma [23]. However, there is limited research on the role of CCL2 in osteosarcoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CCL2-activated macrophages also secrete tissue repair factors, such as TGF-β and VEGF [31]. Numerous studies have shown that the overexpression of CCL2 amplifies many cancer cells' motility and promotes tumor development and metastasis [32][33][34][35][36][37][38], such as chondrosarcoma [22], nasopharyngeal carcinoma [21], and breast carcinoma [23]. However, there is limited research on the role of CCL2 in osteosarcoma metastasis.…”
Section: Discussionmentioning
confidence: 99%